2016
DOI: 10.1177/0192623315625330
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Enrichment Devices on NTP In Vivo Studies

Abstract: The goal of this study was to determine whether the use of nesting material or polycarbonate shelters, as enrichment devices would have an impact on endpoints commonly measured during the conduct of the National Toxicology Program (NTP) 13-week studies. The study design was consistent with the NTP 13-week toxicity studies. Harlan Sprague Dawley (HSD) rats and their offspring, and B6C3F1/N mice were assigned to control (unenriched) and enriched experimental groups. Body weight, food and water consumption, behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Expected changes in clinical pathology, immune function, and histopathology end points were observed in cyclophosphamide-treated animals, with and without nesting material with changes that were similar between animals with and without nesting material. These results, as well as those of another recent study in mice and rats (Churchill et al 2016), showed that adopting measures to improve animal welfare did not have a meaningful impact on clinical pathology end points in mice and rats.…”
Section: Animal Care and Husbandrysupporting
confidence: 66%
“…Expected changes in clinical pathology, immune function, and histopathology end points were observed in cyclophosphamide-treated animals, with and without nesting material with changes that were similar between animals with and without nesting material. These results, as well as those of another recent study in mice and rats (Churchill et al 2016), showed that adopting measures to improve animal welfare did not have a meaningful impact on clinical pathology end points in mice and rats.…”
Section: Animal Care and Husbandrysupporting
confidence: 66%
“…Similarly, no increase in organ weights was detected in C57BL/6JIcoU or BALB/cAnCrRyCpbRivU mice enriched with objects or enriched with nesting material . A more recent study of B6C3F1/N mice further confirmed no significant increase in organ weights (liver, spleen, thymus, adrenal glands, lung, kidneys, and gastrointestinal tract) of either male or female mice when they were provided with nesting material (Crink‐l'Nest TM ) …”
Section: Effects Of Enrichmentmentioning
confidence: 94%
“…Indeed, the environmental enrichment literature has been criticised for inconsistent usage of terms and lack of precise definitions (e.g., [ 36 , 37 ]). Some studies (all from roughly the last decade) refer to the addition of nesting material (to an otherwise barren cage) as enriched (e.g., [ 23 , 38 , 39 ]), although in other studies a cage with nesting material is sometimes used as a condition representing no enrichment (e.g., [ 40 , 41 ]). Other studies refer to cages containing nesting material in addition to other components as their conventional or non-enriched condition (e.g., [ 42 , 43 ]), and many studies do not describe their conventional housing conditions at all [ 21 ], making direct comparisons between studies difficult.…”
Section: Introductionmentioning
confidence: 99%